2010
DOI: 10.4161/cbt.10.4.12441
|View full text |Cite
|
Sign up to set email alerts
|

HIF-1α and HIF-2α correlate with migration and invasion in gastric cancer

Abstract: Hypoxia-inducible factor-1 (HIF-1) is a major determinant of invasion and metastasis in several tumor types. We previously reported that HIF-1α contributed to multidrug resistance in gastric cancer. However, the role of HIF-2α on the progression of gastric cancer is seldom reported. In this study, we first examined the possible role of HIF-1α and HIF-2α in the process of invasiveness and metastasis of gastric cancer, using immunohistochemistry of 80 gastric cancer tissues, western blot and real-time PCR of 8 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
42
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 34 publications
5
42
1
1
Order By: Relevance
“…Although hypoxia is cytotoxic to both normal and cancer cells, some cancer cells acquire characteristics that allow them to survive and grow under hypoxic conditions (such as, expression of angiogenic factors, glycolytic enzymes and stress proteins). In addition, these ischemic conditions contribute to the aggressive metastatic phenotypes of tumor cells, and metastasis, which is characterized by migration, seeding and growth of satellite lesions in specific organs, is commonly considered to be the final stage of cancer (11,(31)(32)(33)(34). Experimental and clinical data provided evidence for a relationship between intratumoral hypoxia and aggressive behavior in solid tumors, including gastric cancer (35)(36)(37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although hypoxia is cytotoxic to both normal and cancer cells, some cancer cells acquire characteristics that allow them to survive and grow under hypoxic conditions (such as, expression of angiogenic factors, glycolytic enzymes and stress proteins). In addition, these ischemic conditions contribute to the aggressive metastatic phenotypes of tumor cells, and metastasis, which is characterized by migration, seeding and growth of satellite lesions in specific organs, is commonly considered to be the final stage of cancer (11,(31)(32)(33)(34). Experimental and clinical data provided evidence for a relationship between intratumoral hypoxia and aggressive behavior in solid tumors, including gastric cancer (35)(36)(37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
“…Intratumoral hypoxia is a common feature of solid tumors and an important microenvironmental factor that drives aggressive behavior in cancer (9,11). After being exposed to hypoxia, several types of cancer cells increase their synthesis of a protein called hypoxia-inducible factor (HIF), which in turn binds to and transactivates target genes (12).…”
Section: Introductionmentioning
confidence: 99%
“…HIF is a heterodimer consisting of an oxygen-dependent α subunit and a constitutively expressed β subunit (9). Previous studies have demonstrated that HIF-1α is overexpressed in gastric cancer (13)(14)(15); furthermore, HIF-1α is associated with metastatic potential in gastric cancer cells via undefined underlying mechanisms (10).…”
Section: Introductionmentioning
confidence: 99%
“…Hypoxic tumor microenvironments induce phenotypic changes that make cancer cells aggressive (9,10), refractory to treatment (11) and likely to metastasize (12). These phenotypic changes are mediated by hypoxia-inducible factors (HIFs) (12).…”
Section: Introductionmentioning
confidence: 99%
“…HIF-1 upregulation is an early event of cells in hypoxia that triggers hypoxia-related gene transcription (6). HIF-1 can promote tumor angiogenesis, drug resistance and cell migration by binding with downstream HRE (7,8).…”
Section: Introductionmentioning
confidence: 99%